THE EFFECT OF SOLIDING ACCELERATING ADDITIVES ON THE MAIN PROPERTIES OF FOAM CONCRETE - Egamberdiyeva, Tutiyo (Новости образования: исследование в XXI веке, 2023)
Foam concrete appeared in the domestic market a long time ago, but even though foam blocks have been used in Europe for more than ten years, many consumers still have questions about the quality of foam, reliability and environmental material. is not aware of what happened, but the whole point is the unconventionality of new materials in domestic consumption. Foam concrete is one of the progressive and promising construction materials that are increasingly used in residential construction around the world. It meets modern requirements for heat protection. The use of foam concrete products can reduce the consumption of materials, labor and construction costs.